2013
DOI: 10.3109/09537104.2013.827781
|View full text |Cite
|
Sign up to set email alerts
|

Variability of on-treatment platelet reactivity in patients on clopidogrel

Abstract: Response to clopidogrel therapy is subject to inter-individual variability. However, data with regard to on-treatment platelet reactivity over time in patients undergoing coronary stenting are scarce. For this prospective observational study, 102 consecutive patients on dual antiplatelet therapy undergoing coronary stenting due to stable coronary artery disease (CAD; n = 29), non ST-elevation acute coronary syndrome (NSTE-ACS; n = 45) and ST-elevation myocardial infarction (STEMI; n = 28) were enrolled. Vasodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
2
12
0
1
Order By: Relevance
“…The reason for the divergent results is not evident, but differences in study patient characteristics, (like age, comorbidity, other medication and proportion of patients with STEMI/ NSTE ACS) as well as timing of measurement and time of follow-up may be important factors. Important individual change in HPR status through 6-months follow-up, in patients treated with clopidogrel, has also been observed with other methods (26). Our data are in line with earlier data indicating a substantial change in individual HPR status over time, in patients treated with clopidogrel.…”
Section: Discussionsupporting
confidence: 91%
“…The reason for the divergent results is not evident, but differences in study patient characteristics, (like age, comorbidity, other medication and proportion of patients with STEMI/ NSTE ACS) as well as timing of measurement and time of follow-up may be important factors. Important individual change in HPR status through 6-months follow-up, in patients treated with clopidogrel, has also been observed with other methods (26). Our data are in line with earlier data indicating a substantial change in individual HPR status over time, in patients treated with clopidogrel.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the widespread use of clopidogrel, there is a rate of recurrent cardiovascular (CV) events of at least 10% within 1 year of an ACS event . These events are potentially explained by issues related to clopidogrel including variability in antiplatelet response, pharmacogenomic influences, and drug interactions . The P2Y 12 ‐receptor inhibitor prasugrel overcame a number of limitations of clopidogrel but has a similar chemical structure (thienopyridine).…”
mentioning
confidence: 99%
“…A number of studies have performed longitudinal analyses of PR in clopidogrel-treated patients over time, and the results have again been discrepant [1,26,[32][33][34][35][36][37][38]. However, these studies investigated heterogeneous patient populations managed with different antiplatelet regimens and in whom platelet function testing was performed at varying intervals in relation to both clopidogrel loading and timing of PCI.…”
Section: Discussionmentioning
confidence: 99%
“…PRU and AUC15 ADP ), and in rates of HTPR while receiving clopidogrel from baseline. Increasingly, it is becoming recognized that prevalence of HTPR can vary significantly over time among clopidogrel-treated patients undergoing PCI [32,34,36,37]. For example, a study performed in 102 patients with stable CAD or ACS (including STEMI) showed that rates of HTPR as measured by the vasodilator-stimulated phosphoprotein-phosphorylation assay reduced significantly from 67% at baseline (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation